1999
DOI: 10.1046/j.1442-200x.1999.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and diagnosis in Japanese patients with Wilson's disease

Abstract: None of the observed mutations, except for 2302insertion(ins)C, have been previously detected in either European or North American patients. We conclude that the mutation spectrum of Wilson's disease may thus indicate a population-dependent pattern. Based on the population-dependent manner of the occurrence of ATP7B gene mutations, it may be possible to establish a molecular diagnosis system. A molecular diagnosis system is considered to be very effective for making a definitive diagnosis in very young patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Both mutations were not detected in our patients. The onset of WND in neurological and hepatic patient was same as reported earlier that hepatic disorders are major symptoms during childhood and neuropathy becomes evident during adolescence (Shimizu and Nakazono, 1999;Ferenci, 2001;Roberts and Schilsky, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…Both mutations were not detected in our patients. The onset of WND in neurological and hepatic patient was same as reported earlier that hepatic disorders are major symptoms during childhood and neuropathy becomes evident during adolescence (Shimizu and Nakazono, 1999;Ferenci, 2001;Roberts and Schilsky, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…The rest of the mutations are highly variable. Most mutations lie on exons 8, 12, 13, 16, and 18 in Northern Chinese covering 60.5-74% mutations (Liu et al 2004;Wu et al 2001);exons 8, 12, 13, 16, and 18 in Taiwanese with coverage of 61.8% (Wan et al 2006); exons 8, 11, and 18 in Koreans with coverage of 59.8-71.4% (Park et al 2007;Yoo 2002);and exons 5, 8, 12, 13, and 18 in Japanese with coverage of 60.9-70% (Okada et al 2000;Shimizu et al 1999). We proposed a five-exon screening approach to Hong Kong Han Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, WD is the most common inherited liver disease in Hong Kong Han Chinese. The mutation spectrum of the ATP7B gene is population specific even within East Asia (Ferenci 2006;Kenney and Cox 2007;Lee et al 2000;Park et al 2007;Shimizu et al 1999;Wan et al 2006). Therefore, data from other areas cannot be directly applicable for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Gene analysis Structural analysis of the causal gene (ATP7B) for the disease was performed for three patients in family 1 and one in family 2, after obtaining informed consent. Genomic DNA was extracted from the peripheral blood, and each exon of the ATP7B gene was amplified by polymerase chain reaction (PCR) (Shimizu et al 1995(Shimizu et al , 1999. Nine exons (exon 5, 8, 10, 11, 12, 13, 14, 16, and 18) were selected for the first analysis on the basis of previous studies (Shimizu et al 1995(Shimizu et al , 1999Takeshita 2000;Yamaguchi et al 1998;Okada et al 2000), which had demonstrated a higher frequency of mutations in specific exons of the ATP7B gene of Japanese patients with Wilson disease.…”
Section: Familymentioning
confidence: 99%